Filippo Pennacchio, Il romanzo global. Uno studio narratologico (ENTHYMEMA, 2019)
Review of Filippo Pennacchio, Il romanzo global. Uno studio narratologico.
Keywords: Global novel; Pennacchio; Postmodernism; Narratology